Single dose oral ketoprofen and dexketoprofen for acute postoperative pain in adults - Barden, Jodie (2009)
BACKGROUND: Ketoprofen is a non-selective non-steroidal anti-inflammatory drug (NSAID) used to treat acute and chronic painful conditions. Dexketoprofen is the (S)-enantiomer, which is believed to confer analgesia. Theoretically dexketoprofen is expected to provide equivalent analgesia to ketoprofen at half the dose, with a consequent reduction in gastrointestinal adverse events. OBJECTIVES: To assess efficacy, duration of action, and associated adverse events of single dose oral ketoprofen and dexketoprofen in acute postoperative pain in adults. SEARCH METHODS: We searched Cochrane CENTRAL, MEDLINE, EMBASE and the Oxford Pain Relief Database for studies to August 2009. SELECTION CRITERIA: Randomised, double blind, placebo-controlled trials of single dose orally administered ketoprofen and dexketoprofen in adults with moderate to severe acute postoperative pain. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. Pain relief or pain intensity data were extracted and converted into the dichotomous outcome of number of participants with at least 50% pain relief over 4 to 6 hours, from which relative risk and number-needed-to-treat-to-benefit (NNT) were calculated. Numbers of participants using rescue medication over specified time periods, and time to use of rescue medication, were sought as additional measures of efficacy. Information on adverse events and withdrawals was collected. MAIN RESULTS: Fourteen studies compared ketoprofen (968 participants) at mainly 25 mg and 50 mg with placebo (520 participants). Seven studies compared dexketoprofen (681 participants) at mainly 10 mg to 25 mg with placebo (289 participants). Studies were of adequate reporting quality, and participants had pain following dental, orthopaedic, obstetric, gynaecological and general surgery. There was considerable clinical heterogeneity between studies in dental and other types of surgery, particularly bunionectomy, which limited analysis. Ketoprofen at doses between 12.5 mg and 100 mg produced NNTs for at least 50% pain relief over 4 to 6 hours of 2.4 to 3.3. For dental studies only there was a trend to more efficacy at higher doses, with NNT decreasing from 2.4 at 12.5 mg to 1.6 at 100 mg. Dexketoprofen at doses of 10/12.5 mg and 20/25 mg produced NNTs for at least 50% pain relief over 4 to 6 hours of 3.2 and 3.6, with no obvious dose response. Significantly fewer participants used rescue medication with ketoprofen and dexketoprofen than placebo. The median time to remedication was about 5 hours with ketoprofen and 4 hours with dexketoprofen. The expected equivalent efficacy with a half dose of dexketoprofen compared to ketoprofen was not demonstrated. Adverse events were uncommon with both drugs, and not significantly different from placebo. AUTHORS’ CONCLUSIONS: Ketoprofen at doses of 25 mg to 100 mg is an effective analgesic in moderate to severe acute postoperative pain with an NNT for at least 50% pain relief of 3.3 with a 50 mg dose. This is similar to that of commonly used NSAIDs such as ibuprofen (NNT 2.5 for 400 mg dose) and diclofenac (NNT 2.7 at 50 mg dose). Duration of action is about 5 hours. Dexketoprofen is also effective with NNTs of 3.2 to 3.6 in the dose range 10 mg to 25 mg. Both drugs were well tolerated in single doses.